Young Entrepreneur Financial Planning Training (Pkpm) During the Covid 19 Pandemic - Purnomo, Agus; Purnamasari, S.; Hani, Umi; Zahra Maulida, Atika (Amala Jurnal Pengabdian Kepada Masyarakat, 2023)
Wealth is something that is very dharuri in human life, Islam has clearly regulated the management of wealth both personally and publicly. With possessions, humans can meet the needs of life both material and immaterial. The concept of Islamic Financial Planning (Sharia) or Islamic Financial Planning has a universal nature that can not only be applied to entrepreneurs during the Covid 19 virus pandemic so that business actors can plan products and finances when the Covid 19 virus outbreak hits the Indonesian homeland. In financial planning, entrepreneurs are able to provide training and financial preparation when experiencing a decrease in sales or a decrease in income due to the outbreak of the Covid-19 virus which results in a decrease in business performance and a decrease in business performance in financial design in the form of business and non-business. The implementation of this service activity is using training methods on how to prepare financial planning, marketing preparation, preparation of product quality results with the aim of being able to maintain business during the outbreak of the covid 19 virus.The outcome of this service activity is that business actors can plan finances, sales / marketing, and produce quality products that can compete in the market during the disaster of the covid 19 virus outbreak so that, A business that can survive and not suffer losses when a virus outbreak strikes.